Students’ Attitude towards Learning Management System in Ambrose Alli University, Ekpoma - Edobor, Priscilla Eghonghon; Igbinovia, Magnus Osahon; Audu, Faith Oshuware (Communicate: Journal of Library and Information Science, 2023)
The introduction of Learning Management System (LMS) into Nigerian universities has altered the way learning takes place. As such, it is crucial to assess the attitude of students towards this system for subsequent use. Consequently, two research questions were raised to guide the study. The study adopted descriptive research design for a population comprising of 10,081 undergraduate students from three selected faculties (Education, Life Sciences and Physical Sciences) in Ambrose Alli University, Ekpoma. Yamane (1967) Table for determining sample size was used to select a sample size of 200 distributed proportionately across the three faculties. Structured questionnaire was used to elicit data from the respondents and 100% response rate was achieved. The data was analyzed using descriptive statistics of frequency, percentage and mean. The findings of the study revealed that the respondents had positive attitude towards LMS ( = 3.3) which is predominantly due to the comfort they experience when using LMS for academic purposes. The study also found that some of the factors affecting attitude towards utilization of LMS were quality of content/material ( = 3.6), quality of visuals and audibility for multimedia content ( = 3.5) and personal values/attributes/ characteristics of the students content ( = 3.5). The study concluded that the excitement of young adult towards technology makes them want to explore technological devices stimulating comfort, optimism, independence and ease with using LMS. The authors thereafter made recommendations based on factors militating against use of LMS.